Study of municipal solid waste incinerator bottom ash (MSWIBA) and coal fly ash (CFA) applied to concrete pavement bricks: Mechanical properties, microstructure, durability - Yudong Zhang; Yuzhen Li; Huifang Zhang; Zhenwei Jiang; Yuhong Huang; Fan Jia; Ziyang Zong (Case Studies in Construction Materials, 2025)
The increasing production of municipal solid waste incineration bottom ash (MSWIBA) and coal fly ash (CFA) has not been fully utilized, thus contributing to environmental burdens. To conserve natural resources and promote resource recycling, this study investigates the use of MSWIBA with a particle size of 1.18–2.36 mm to replace river sand of 0 %, 10 %, 20 %, 30 %, and 40 %,CFA to replace cement of 0 %, 5 %, 10 %, 15 %, and 20 % in concrete pavement bricks to determine the optimal substitution rates. The study evaluates the mechanical properties, microstructure, and durability (freeze-thaw resistance, sulfate resistance, and heavy metal leaching) of concrete pavement bricks samples to identify the optimal replacement levels for maximizing their utility. Additionally, the environmental and economic benefits of these concrete pavement bricks formulations are assessed. The study results indicated that the concrete pavement brick samples with 5 % CFA and 10 % MSWIBA or 10 % CFA and 20 % MSWIBA achieved superior mechanical performance, among which concrete pavement brick samples, BA20FA10 had the best mechanical properties, the 28-day compressive strength and flexural strength reached 52.8 MPa and 6.2 MPa, respectively. At these substitution rates, the water absorption curves of the samples exhibit three distinct phases: a sharp drop, followed by a slower descent, and ultimately a steady state phase. Furthermore, the concrete pavement brick samples also demonstrated excellent freeze-thaw and sulfate resistance, with low heavy metal leaching. Pore structure analysis reveals that the incorporation of MSWIBA and CFA effectively refines the pore structure. The use of MSWIBA as a replacement for fine aggregates and CFA as a cement replacement complies with the goals of sustainable use and environmentally responsible management of MSWIBA and CFA.